Management of agricultural soils for greenhouse gas mitigation: Learning from a case study in NE Spain. (1st April 2016) - Sánchez, B.; Iglesias, A.; McVittie, A.; Álvaro-Fuentes, J.; Ingram, J.; Mills, J.; Lesschen, J.P.; Kuikman, P.J.
Abstract: A portfolio of agricultural practices is now available that can contribute to reaching European mitigation targets. Among them, the management of agricultural soils has a large potential for reducing GHG emissions or sequestering carbon. Many of the practices are based on well tested agronomic and technical know-how, with proven benefits for farmers and the environment. A suite of practices has to be used since none of the practices can provide a unique solution. However, there are limitations in the process of policy development: (a) agricultural activities are based on biological processes and thus, these practices are location specific and climate, soils and crops determine their agronomic potential; (b) since agriculture sustains rural communities, the costs and potential for implementation have also to be regionally evaluated and (c) the aggregated regional potential of the combination of practices has to be defined in order to inform abatement targets. We believe that, when implementing mitigation practices, three questions are important: Are they cost-effective for farmers? Do they reduce GHG emissions? What policies favour their implementation? This study addressed these questions in three sequential steps. First, mapping the use of representative soil management practices in the European regions to provide a spatial context to upscale the local results. Second, using a Marginal Abatement Cost Curve (MACC) in a Mediterranean case study (NE Spain) for ranking soil management practices in terms of their cost-effectiveness. Finally, using a wedge approach of the practices as a complementary tool to link science to mitigation policy. A set of soil management practices was found to be financially attractive for Mediterranean farmers, which in turn could achieve significant abatements (e.g., 1.34 MtCO2 e in the case study region). The quantitative analysis was completed by a discussion of potential farming and policy choices to shape realistic mitigation policy at European regional level. Graphical abstract: Highlights: Sustainable management of agricultural soils can reduce significantly GHG emissions. Marginal abatement costs curve evaluates the cost-effectiveness of farming practices. We use a wedge approach to inform regional mitigation policy. The main barrier to implementation is the limited practical demonstration.